Immunomodulatory effects of curcumin on macrophage polarization in rheumatoid arthritis - Deng, Tingting; Xu, Jiahe; Wang, Qiong; Wang, Xing; Jiao, Yi; Cao, Xiaoxue; Geng, Qishun; Zhang, Mengxiao; Zhao, Lu; Xiao, Cheng (Frontiers in Pharmacology, 2024)
Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by synovial inflammation, cartilage destruction, pannus formation and bone erosion. Various immune cells, including macrophages, are involved in RA pathogenesis. The heterogeneity and plasticity of macrophages render them pivotal regulators of both the induction and resolution of the inflammatory response. Predominantly, two different phenotypes of macrophages have been identified: classically activated M1 macrophages exacerbate inflammation via the production of cytokines, chemokines and other inflammatory mediators, while alternatively activated M2 macrophages inhibit inflammation and facilitate tissue repair. An imbalance in the M1/M2 macrophage ratio is critical during the initiation and progression of RA. Macrophage polarization is modulated by various transcription factors, epigenetic elements and metabolic reprogramming. Curcumin, an active component of turmeric, exhibits potent immunomodulatory effects and is administered in the treatment of multiple autoimmune diseases, including RA. The regulation of macrophage polarization and subsequent cytokine production as well as macrophage migration is involved in the mechanisms underlying the therapeutic effect of curcumin on RA. In this review, we summarize the underlying mechanisms by which curcumin modulates macrophage function and polarization in the context of RA to provide evidence for the clinical application of curcumin in RA treatment.